2000
DOI: 10.1128/iai.68.6.3541-3547.2000
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Structure for F1C Fimbriae of Uropathogenic Escherichia coli

Abstract: F1C fimbriae are correlated with uropathogenic Escherichia coli strains. Although F1C fimbriae mediate binding to kidney tubular cells, their receptor is not known. In this paper, we demonstrate for the first time specific carbohydrate residues as receptor structure for F1C-fimbria-expressing E. coli. The binding of the F1C fimbriated recombinant E. coli strain HB101(pPIL110-54) and purified F1C fimbriae to reference glycolipids of different carbohydrate compositions was evaluated by using thin-layer chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 54 publications
2
70
0
2
Order By: Relevance
“…Type 1 fimbriae bind to mannose-containing receptors, and the P group fimbriae bind to the Gal␣(1-4)Gal moiety of the P blood group and related receptors, which are widely distributed on the uroepithelium (31). The high-affinity binding of F1C fimbriae to the GalNAc␤1-4Gal␤ sequence of glycolipids, asialo-GM 1 (GgO 4 Cer) and asialo-GM 2 (GgO 3 Cer), and low-affinity binding to carbohydrate structures GlcNAc␤1-3Gal␤, Gal␤1-4Glc, Gal, and Glc of glycolipids have been demonstrated recently (15).…”
Section: Discussionmentioning
confidence: 97%
“…Type 1 fimbriae bind to mannose-containing receptors, and the P group fimbriae bind to the Gal␣(1-4)Gal moiety of the P blood group and related receptors, which are widely distributed on the uroepithelium (31). The high-affinity binding of F1C fimbriae to the GalNAc␤1-4Gal␤ sequence of glycolipids, asialo-GM 1 (GgO 4 Cer) and asialo-GM 2 (GgO 3 Cer), and low-affinity binding to carbohydrate structures GlcNAc␤1-3Gal␤, Gal␤1-4Glc, Gal, and Glc of glycolipids have been demonstrated recently (15).…”
Section: Discussionmentioning
confidence: 97%
“…The presence of S fimbriae and type 1C fimbriae (172,178,340). Uropathogenic P. mirabilis isolates also contain a member of the ␥ 1 -fimbrial clade, the ambient-temperature fimbria (atf) operon; however, the encoded adhesin is not required for cystitis in a mouse model (213,214,373).…”
Section: The ␥-Fimbriaementioning
confidence: 99%
“…F1C fimbriae are expressed by a large proportion of UTI E. coli strains; depending on the study, 14 to 30% of UTI strains have been reported to be able to express these fimbriae (47,60). F1C fimbriae specifically recognize galactosylceramide targets present on epithelial cells in the kidneys, ureters, and bladder, as well as globotriaosylceramide, present only in the kidneys (4,29). Recently, it was shown that human renal epithelial cells specifically produce the proinflammatory cytokine interleukin-8 in response to F1C fimbria-mediated attachment (4).…”
Section: Strain 83972 Does Not Trigger Host Defense Mechanisms and Lamentioning
confidence: 99%